⎩ ⎨ ⎧ 2 y − x ( x + y ) = 1 ( x + y ) x − y = 2
Let ( x 1 , y 1 ) , ( x 2 , y 2 ) , … , ( x n , y n ) denote all the solutions of ( x , y ) that satisfy the system of equations above.
Find i = 1 ∑ n ( x n + y n ) to 3 decimal places.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Brian Charlesworth Yes you are right Sir!! I myself stopped after finding the two equations of x+y.....
Problem Loading...
Note Loading...
Set Loading...
From the first equation we have that x + y = 2 x − y . Substituting into the second equation, we have that
( x + y ) x − y = ( 2 x − y ) x − y = 2 ⟹ 2 ( x − y ) 2 = 2 ⟹ ( x − y ) 2 = 1 ⟹ x − y = ± 1 .
If x − y = 1 then from the second equation x + y = 2 , giving us ( x , y ) = ( 2 3 , 2 1 ) .
If x − y = − 1 then ( x + y ) − 1 = 2 ⟹ x + y = 2 1 , giving us ( x , y ) = ( − 4 1 , 4 3 ) .
The desired sum is then 2 3 + 2 1 − 4 1 + 4 3 = 2 5 = 2 . 5 .
Note that we didn't really need to solve for ( x , y ) as the only two cases involved gave us x + y = 2 and x + y = 2 1 , which was all we needed to determine that the desired sum was 2 . 5 .